Modeling of the functioning of territorial systems with the purpose of identification of problem situations - Lisitskiy, Vasiliy; Gernet, Nadezhda (Eastern-European Journal of Enterprise Technologies, 2018)
The purposeful territorial system (country, region), containing production, consumption, management, and environmental spheres is considered. In the process of system functioning, problem situations arise. The method for modeling the functioning of a territorial system by a complex of interacting linear programming problems, reflecting the inextricable link between the mechanism of centralized planning of production and consumption of goods, resources and the mechanism of market pricing is developed. The dependence of system characteristics of the cyclical dynamics on spectral properties of the generalized technological matrices of circulation of goods and resources is proved. The obtained results are relevant for modern Ukraine, other transitional national economies, characterized by an increased occurrence of problem situations. In this case, the territorial system can come very close to the bifurcation point, in which an alternative to further development arises. The choice of any alternative immerses the territorial system in the transition period. To identify problem situations, it is proposed to form the generalized technological matrixes of circulation of goods and resources on the basis of reporting data, to determine their majorizing roots that characterize the structural stability of the system. It is shown that the right and left eigenvectors found, corresponding to the majorizing matrix roots, determine the effective structures of supply of goods, resources and market prices for them. The system of informative features that determine the deviations of the actual characteristics of the territorial system from efficient ones is constructed. The proposed system of features makes it possible to detect national economic disparities that give rise to problem situations. Classes of problem situations are distinguished. The class contains problem situations for which the overall technology for their resolution is effective. This allowed assigning a standard case to each class that sets the reference problem situation and the way to resolve it (using an adequate pricing technology, adjusting the structure of the minimum needs of the population, the structure of available resources, forming the main properties of the system). The obtained results can serve as a platform for creating the information technology of detection and identification of problem situations, which implements the case-based reasoning technology.